Constitutional and mosaic large NF1 gene deletions in neurofibromatosis type 1. Issue 6 (June 1998) - Rasmussen, S A; Colman, S D; Ho, V T; Abernathy, C R; Arn, P H; Weiss, L; Schwartz, C; Saul, R A; Wallace, M R
Abstract : A set of neurofibromatosis type 1 (NF1) patients was screened for large NF1 gene deletions by comparing patient and parent genotypes at 10 intragenic polymorphic loci. Of 67 patient/parent sets (47 new mutation patients and 20 familial cases), five (7.5%) showed loss of heterozygosity (LOH), indicative of NF1 gene deletion. These five patients did not have severe NF1 manifestations, mental retardation, or dysmorphic features, in contrast to previous reports of large NF1 deletions. All five deletions were de novo and occurred on the maternal chromosome. However, two patients showed partial LOH, consistent with somatic mosaicism for the deletion, suggesting that mosaicism may be more frequent in NF1 than previously recognised (and may have bearing on clinical severity). We suggest that large NF1 deletions (1) are not always associated with unusual clinical features, (2) tend to occur more frequently on maternal alleles, and (3) are an important mechanism for constitutional and somatic mutations in NF1 patients.